Analisis Struktur dan Kebahasaan pada Kumpulan Cerita Anekdot serta Rekomendasinya sebagai Modul Ajar Teks Anekdot Tingkat SMA Kelas X Fase E: Analysis of Structure and Linguistic Features in Anecdote Story and Its Recommendation as a Teaching Module for Anecdote Text At High School Class X Phase E - Yudha Sanjaya; Ferina Meliasanti; Dewi Herlina (Universitas Tidar, 2026)
This research analyzes the structure and linguistic features of anecdote texts in the book